Eat your science homework : recipes for inquiring minds - Staats, Ann McCallum, 1965-; Hernandez, Leeza (Watertown, MA : Charlesbridge, 2014)
Hungry readers discover recipes in this companion to Eat Your Math Homework. A main text explains upper-elementary science concepts, including subatomic particles, acids and bases, black holes, and more. Alongside simple recipes, side-bars encourage readers to also experiment and explore outside of the kitchen.
Discovering delicious: The scientific method -- Safety in the lab ... er, kitchen -- Let's talk tiny: Atoms and molecules -- Atomic popcorn balls -- We don't mean to be dense: Properties of matter -- Density dressing and veggie sticks -- Now you see it, now you don't: chemical reactions -- Invisible ink roll-over snacks -- Give it a whorl: Inherited traits -- Loop, whorl, and arch cookies -- Harden, morph, squash: Rocks and minerals -- Sedimentary pizza lasagna -- Hot stuff: Volcanoes and heat -- Mashed potato lava cakes -- A hole lot of space: Our solar system -- Black hole breakfast swallow-ups -- Science review.
Includes index.
Ages 7-10.
A Junior Library Guild Selection.
Keywords: Science -- Experiments -- Juvenile literature; Food -- Experiments -- Juvenile literature; Food -- Composition -- Juvenile literature; Cooking -- Experiments -- Juvenile literature; Science -- Experiments; Food -- Experiments; Food -- Composition; Cooking -- Experiments; Children's nonfiction; Picture books; Juvenile works; Picture books